Employees' Emotional Reactions to Customer Deal Requests. Issue 2 (2nd April 2016) - Gillison, Stephanie T.; Northington, William Magnus; Beatty, Sharon E.
Abstract : Customers are increasingly asking for discounts and deals while shopping in traditional retail stores. Using interviews and a survey of frontline employees, this article develops and tests a model that profiles the effect of customer deal requests on employees' emotional reactions. The findings show that employees' request self-efficacy and their positivity toward deal requesters increase their comfort with these deal requests. This comfort, along with the employee's perceptions of the dominance of the customer's approach style and the reasonableness of the request, impacts the employee's affective reactions following deal requests. Script theory and motivated reasoning are used to explain this process, while the importance of employee comfort in this process is emphasized. Implications for theory and management are discussed.